An improved switching and control technique in polarization and depolarization current measurement applications - Kasri, Nur Faizal (2014)
Polarization and Depolarization Current (PDC) measurement is one of the methods used to assess the insulation conditions of the High Voltage (HV) apparatus. PDC testing is a non-destructive dielectric diagnostic testing technique employed to determine the conductivity and moisture content of electric insulators. Due to rapid and advancing changes in insulation material technology, an improvement of the PDC measurement system is required to cope with new and emerging materials. Thus, the reliability of the PDC measuring system to accurately measure and record the charging and discharging currents is a crucial factor that cannot be overemphasized. Therefore, in this study, a PDC measurement switching circuit was designed and simulated using the Multisim 10 software and practically tested in order to obtain accurate and reliable results. The design included the reduction of HV relays from four to two, introduction of a safety feature to protect the electrometer and a LabVIEW software programme to control switching activity and data recording. A user friendly Graphic User Interface (GUI) was provided to make the programme user friendly. Furthermore, the study included the construction and testing of the simulated PDC switch. When the switch was tested on some insulation materials that included polymeric, cellulose and liquid insulators, the result shows that this system is able to accurately replicate the popularly known and accepted PDC pattern and also measure the polarization current (idp) and depolarization current (ip) of some of these materials in Pico-amperes (x 10-12 A). The validity and reliability of this system were ratified after conduction of these tests. It is concluded that the experimental and theoretical PDC current response patterns are comparable and thus this system is reliable, and the results produced are valid for further analysis.